Penguatan Literasi Subjective Well Being dan Kemandirian Santri melalui Psikoedukasi Adab Belajar dan Dukungan Sebaya - Muhammad Cholid Abdurrohman; Saiful Muktiali; Siti Juariah; Rini Setyowati; Iklima Sanubari (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Adolescents in Islamic boarding schools are often confronted with dual academic demands that may trigger mental fatigue and threaten their subjective well-being. Therefore, mastery of learning ethics (adab) and self-regulation skills is considered essential for maintaining students’ psychological resilience and academic adjustment. This community service program aimed to strengthen students’ psychological capacities through a participatory psychoeducational intervention. The program integrated Islamic learning ethics with contemporary educational psychology while accommodating differentiated learning approaches. To ensure measurement validity, the cognitive evaluation instrument was developed through a content validity approach by adapting the fundamental principles of standardized psychological scales. The data were then analyzed using the Normalized Gain (N-Gain) method. The findings revealed that the psychoeducational intervention was highly effective, achieving an overall average N-Gain score of 0.79 (high category). The most substantial improvement was observed in peer-support awareness (peer counseling), with an N-Gain score of 0.87, increasing from 72.73% to 96.40%. The remaining indicators, learning ethics, self-regulated learning, and subjective well-being, demonstrated moderate gains (0.52–0.69), which can be attributed to the participants’ relatively high baseline scores (ceiling effect). The intervention successfully enhanced students’ understanding of peer support and constructive coping strategies. Accordingly, this psychoeducational model is recommended for continuous integration into Islamic boarding school dormitory curricula to foster resilient, self-regulated, and ethically grounded students.